2019
DOI: 10.1007/s00167-019-05595-z
|View full text |Cite
|
Sign up to set email alerts
|

Customised bi-compartmental knee arthroplasty shows encouraging 3-year results: findings of a prospective, multicenter study

Abstract: Purpose The purpose of this study was to assess the clinical and patient-reported outcomes of a customised, individually made (CIM) bi-compartmental knee arthroplasty (BKA). Methods A prospectively recruited cohort of 79 patients was implanted with a CIM-BKA (patello-femoral plus either medial or lateral tibio-femoral, iDuo G2 system, Conformis, Billerica MA) at eight centres in the US and Germany. Patients were assessed for the 2011 KSS, KOOS, and ROM pre-operatively and at 2 weeks, 6 weeks, 12 weeks, 1 year,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…However, the modular implant is time-and technique-demanding and requires a high level of surgical expertise due to the multiple instrumentation and orientations with the multiple implants. 18,19 An advantage of the monolithic implant is possibly easier implementation for the surgeon, but the survivorship is unacceptable. 15 Another potential solution is patient-specific customized monolithic implants which have promising early survivorship and short-term results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the modular implant is time-and technique-demanding and requires a high level of surgical expertise due to the multiple instrumentation and orientations with the multiple implants. 18,19 An advantage of the monolithic implant is possibly easier implementation for the surgeon, but the survivorship is unacceptable. 15 Another potential solution is patient-specific customized monolithic implants which have promising early survivorship and short-term results.…”
Section: Discussionmentioning
confidence: 99%
“…A single published study has supported improved patient-reported outcome scores and acceptable early component survival with CIM CR bicompartmental knee arthroplasty. 18 The kinematic performance of CIM implant systems may be impacted by the accuracy of the three-dimensional component femoral and tibial implant placement during TKA. Pairing of CIM-CR implant systems with patient-specific instrumentation (PSI) offers the potential to increase precision and accuracy in component placement.…”
mentioning
confidence: 99%
“…Improvements in knee mobility, as well as in knee scores (KSS and KOOS) were observed. Ninety-seven percent of implants survived after 2.6 years [ 73 ]. Ogura et al could confirm these results, showing a survival rate of 98% after 2 years and 92% after 5 years.…”
Section: Resultsmentioning
confidence: 99%